3D printing, policing and crime. (2nd January 2021) - Daly, Angela; Mann, Monique; Squires, Peter; Walters, Reece
ABSTRACT: This article examines the implications of advanced manufacturing technology, more commonly known as three dimensional (3D) printing, for policing and crime, notably the dissemination of digital design files and the use of 3D printers to produce illicit firearms. The application and rapid evolution of 3D printing technology has created new challenges for law and regulation, and represents an interesting security paradox, albeit one which until now has received scant attention in the criminological or policing literature. On the one hand, 3D printing denotes a significant shift in the creation and use of objects, ranging from food to body parts, and more controversially, weaponry. On the other hand, the use of this technology to create items such as firearms and weapons signifies a potential safety, security, and legal challenge. We explore the emergence of 3D printing and its use to create firearms along with the theoretical challenges to legal design and enforcement presented by this decentralised technology. We also present some empirical data on instances of 3D printed firearms and firearm parts being detected internationally, and some jurisdictions' legal and policy responses. We conclude by considering that any regulation of 3D printed firearms must be based on a robust evidence base and take proper account of citizens' rights, but also that any national regulation will be in tension with the transnational and decentralised nature of the technology.